Effects of Cleft and It’s Clinical Implications - Sumita Mishra (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most common malformation of the head and neck region affecting individuals and their surroundingsphysically, mentally, psychologically and socially is cleft lip and palate. There are of various types with theirdistinct clinical features and characteristics. Prenatal diagnosis, effective understanding can help formulatea good treatment approach with specialists from various fields working as a team. Parents counseling andfollow up forms the mainstay approach of these children.